Forensic Expertise for Establishing the Causes of Falling Trees - A. V. Antsiferov (Теория и практика судебной экспертизы, 2020)
The article presents the practice of conducting forensic examinations to determine the causes of falling trees by the Centre of wood expertise “ZDOROVY LES”, the most common questions put before experts, the sequence of an expert’s actions as well as it enumerates the causes of falling for damaged trees. The author reviews the list of modern devices needed for the diagnostic of the internal state of trees to detect the dilapidated ones, describes how to use the equipment.